Trait emotional intelligence, forgiveness, and gratitude in Cape Verdean and Portuguese students - Daniela C Wilks (2015)
Trait emotional intelligence, forgiveness, and gratitude are assumed to be theoretically linked with important implications for psychological and social well-being. This study examined the emotional and behavioural dispositional profile of Cape Verdeans and Portuguese by combining together for the first time trait emotional intelligence, emotional intelligence, forgiveness, and gratitude. The sample comprised 327 participants, of whom 119 were Cape Verdean and 208 were Portuguese. The results showed that trait emotional intelligence, willingness to forgive, and gratitude were higher for Cape Verdean compared to Portuguese participants. Lasting resentment was lower among the Cape Verdeans than among the Portuguese. Overall, data suggested that cultural differences might exist across the three constructs examined